Contrition and Community: A Gewirthian Interpretation of State Apologies - Kekewich, Michael (University of Ottawa (Canada), 2010)
This paper provides a philosophical understanding of state apologies by applying Gewirth's deontological theory. Through application of the principle of generic consistency, I contend that a state apology can be understood as a moral obligation concurrent with human rights. Subsequently, I attempt to solidify the Gewirthian understanding of state apology by integrating current understandings of the practice into the Gewirthian model of the community of rights. Here, I also suggest that the psychosocial biography of the community of rights strengthens the Gewirthian interpretation of state apology. Finally, I examine the merits of the U.S. apology for the Tuskegee Syphilis Study from this Gewirthian perspective. Ultimately, I conclude that the Gewirthian application is successful in its ability to clarify the reasons for which state apologies are given, as well as the goals they should accomplish.
Keywords: Ethics.; Philosophy.